NFT METAVERSE STARTUPS AND A POSSIBILITY OF FUNDRAISING THROUGH TOKEN ISSUANCE - Szczukiewicz, Konrad (Management and Administration Journal, 2022)
Blockchain has been one of the leading technology breakthroughs in recent years. It has enabled the creation of multiple cryptocurrencies and tokens which, amongst others, financed the activities of various startup projects. The last few years have seen the emergence of another blockchain-enabled product – Non Fungible Tokens (NFT) which are a digital certificate of ownership. Both NFTs and tokens are wider part of the creation of a metaverse – a new digital, online environment. This article analyses theoretical aspects of cryptocurrencies, tokens, NFTs and metaverse. The fundraising and token issuance aspects are analysed here based on examples of startups Metahero, Ultiarena and Bloktopia.